2016
DOI: 10.13057/biodiv/d170235
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Fish diversity of the Batang Toru River System, South Tapanuli, North Sumatra

Abstract: Roesma DI, Chornelia A, Mursyd A, Kamsi M. 2016. Short Communication: Fish diversity of the Batang Toru River System, South Tapanuli, North Sumatra. Biodiversitas 17: 634-641. A rapid survey on fish diversity was carried in the Batang Toru river system. The survey was carried out in the wet season between 8-14 February 2015 and 15-21 of March 2015 along various tributaries on the east (10) and west (1) side of the main Batang Toru river system. We obtained 427 individuals fish samples consisting of 24 species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…The geographical distinction has triggered the emergence of genetic up to species diversity in the island of Sumatra. This also proved by the results of the research which reported that there are variations in the number of fish species found in 11 tributaries of Batang Toru (North Sumatra) as the main river [35]. It also reported that there is genetic variation intra and inter populations of Tor douronensis (Cyprinidae) from 21 rivers in West Sumatra [36].…”
Section: Resultsmentioning
confidence: 63%
“…The geographical distinction has triggered the emergence of genetic up to species diversity in the island of Sumatra. This also proved by the results of the research which reported that there are variations in the number of fish species found in 11 tributaries of Batang Toru (North Sumatra) as the main river [35]. It also reported that there is genetic variation intra and inter populations of Tor douronensis (Cyprinidae) from 21 rivers in West Sumatra [36].…”
Section: Resultsmentioning
confidence: 63%
“…Hampala macrolepidota was also found in the Batang Toru River (Roesma et al 2016), which differs from the Klawing River only in its flow velocity. The Batang Toru River reportedly had clear water, a flow velocity of 0.85-0.88 m/s, and a substrate of rocks, sand, and gravel; however, the altitudes of the sampling sites were not stated.…”
Section: Fish Distributionmentioning
confidence: 86%
“…Nuryanto et al (2012) detected 22 fish species belonging to 10 families in the Cileumeuh River (Cilacap, Central Java). Roesma et al (2016) detected 24 fish species belonging to 10 families in the Batangtoru River, South Tapanuli, North Sumatra. Yustina (2001) detected 70 species of fish along the Rangau River, Riau, and Sumatra.…”
Section: Species Diversity and Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…These conditions will get worse with the damage of T. douronensis habitat because it will reduce the fitness of Tor population. Roesma et al (2016) strengthened the importance of paying more attention to the water condition in Sumatran Rivers because it is important for Mahseer fish habitat. As this fish species is a migratory species heading to the headwaters for spawning, they need clear and fast flowing water.…”
Section: Resultsmentioning
confidence: 99%